The Efficiency of Public Spending in Sub-Saharan Africa - Wandeda, Dickson O.; Masai, Wafula; Nyandemo, Samuel M. (European Scientific Journal, ESJ, 2021)
In this article, the authors analyze the efficiency of public spending among Sub-Saharan African countries using a panel data for 23 Sub-Saharan Africa countries covering the period 2006-2018. This paper employs two-stage bootstrap output-oriented DEA approach. In addition, this study analyses the sources of distortions in public spending. Results show that the average biascorrected inefficiency score was 48 percent between 2006 and 2018 while the uncorrected inefficiency was 32.3percent. Institutional quality and domestic saving significantly influence the efficiency of public spending. Hence, there is need for Sub-Saharan African governments to observe fiscal discipline through strengthening of monitoring unit of government expenditure.